The Convergence Between Textual Law And Progressive Law In Addressing Contemporary Legal Challenges - Efendie Efendie; Agus Sugiarto; Marsudi Dedi Putra (JURNAL HUKUM SEHASEN, 2024)
This article explores the intersection between textual law and progressive law in the context of resolving contemporary legal challenges. Normative law is the choice for this research, with a case and conceptual approach. Collecting legal materials using literature studies and analyzing them using qualitative descriptive. This research produces: Textual law offers legal certainty through strict interpretation of statutory texts, while progressive law emphasizes substantive justice and adaptation to social change. This analysis identifies how these two approaches can complement each other to create a legal system that is fairer and more responsive, and considers community participation in the legal process. Case studies and theoretical contributions support the argument that combining textual legal principles with progressive legal flexibility can increase the effectiveness of law enforcement in dealing with the complexity and dynamics of law in an era of rapid technological development.